SENACA FL11: a new improved rice variety for Ecuador - CGIAR Research Program on Rice (2019)
Rice variety well adapted to direct seeding in irrigated rice production system in Ecuador, with high amylose, long grain, and loose grains after cooking. The variety has been used by 34,102 farmers between 2014 and 2019.